Procesos morfodinámicos en el torrente Quirio, Chosica, Lima Metropolitana - Meléndez de la Cruz, Juan Felipe (2025)
The eastern area of Metropolitan Lima is characterized by a permanent urban expansion, particularly in the area of Chosica, Lima. In these areas with a semi-arid climate, numerous disasters have occurred due to the exposure of the population to mass movements. A relevant case of this reality is the Quirio torrent (Annex 1. Location), where natural phenomena are reflected in intense water erosion and landslides on hillsides, as well as alluvium in the drainage channel. In this context, informal urban expansion has been taking place in the last 10 years in areas close to the catchment basin of the aforementioned torrent, occupying proluvial fans and slopes. For this reason, it is justified to continue studying these spaces on a large scale to make visible the relationship between the aforementioned phenomena and the exposure and vulnerability of the population. The objective of the research is to know the geology and geomorphology at a scale of 1:5000 to serve as a basis for other studies that consider the exposure and vulnerability of the population within the framework of disaster risk management. The method used is to take into account the theory of geology and geomorphology as part of the Earth Sciences in order to carry out applied work.